Analisis kemampuan koneksi matematika dalam mengerjakan soal cerita - Andi Atmaja; M. Shaefur Rokhman; Wikan Budi Utami (Universitas Muhammadiyah Purworejo, 2020)
The purpose of this article is to describe the mathematical connection ability of students in working on stories on statistics material. This article uses a qualitative approach. The data collection was obtained from the method of documentation, tests, and interview. There are 2 students of class VIII semester II as subjects in this article. The analysis was obtained from the test results of students which consisted of 5 description questions and the results of interviews on 6 indicators of mathematical connection ability. The results of the study obtained that the two students were less capable of applying mathematics in other fields of study or everyday life and the relationships between mathematical topics and between mathematics topics and topics outside mathematics. So it can be concluded that the two students have a poor mathematical connection ability in solving story problems on statistics material.